การปรับตัวของกลุ่มธุรกิจค้าปลีกในภาคตะวันออกเฉียงเหนือสู่การ เป็นประชาคมเศรษฐกิจอาเซียน(The Adaptation of the Retail Business in the Northeast of Thailand for being a Member of the ASEAN Economic Community) - (Apichat Kunthammarak), อภิชาติ คุณธรรมรักษ์; (Sumeth Kaenmanee), สุเมธ แก่นมณี (KKU Research Journal (Graduate Studies) Humanities and Social Sciences, 2015)
การศึกษานี้มีวัตถุประสงค์เพื่อศึกษา 1) ความรู้ความเข้าใจของผู้ประกอบการธุรกิจค้าปลีกในภาค ตะวันออกเฉียงเหนือที่มีต่อประชาคมเศรษฐกิจอาเซียน 2) ระดับการปรับตัวของผู้ประกอบการธุรกิจค้าปลีก ในภาคตะวันออกเฉียงเหนือสู่การเป็นประชาคมเศรษฐกิจอาเซียน และ 3) ปัจจัยเชิงสาเหตุที่มีอิทธิพล ต่อการปรับตัวของผู้ประกอบการธุรกิจค้าปลีกในภาคตะวันออกเฉียงเหนือสู่การเป็นประชาคมเศรษฐกิจอาเซียน โดยทำการเก็บรวบรวมข้อมูลแบบสอบถามผู้ประกอบการธุรกิจค้าปลีก จำนวน 900 คน และประมวลผล โดยใช้โปรแกรมสำเร็จรูป SPSS และ LISREL เพื่อวิเคราะห์ปัจจัยเชิงสาเหตุที่มีผลต่อการปรับตัว ผลการ ศึกษาพบว่า ผู้ประกอบการร้านค้าปลีกมีความรู้ความเข้าใจถึงผลกระทบต่อธุรกิจค้าปลีกของการเกิดประชาคม เศรษฐกิจอาเซียน 3 อันดับแรก ดังนี้ 1) การลงทุนในอาเซียนทำได้โดยเสรี สามารถทำธุรกิจบริการได้โดยเสรี ทำให้ คู่แข่งสามารถเข้ามาแข่งขันได้ถึงในประเทศไทย 2) การลงทุนในอาเซียนทำได้โดยเสรี สามารถย้ายฐาน การผลิตไปยังประเทศที่เหมาะเป็นแหล่งผลิต เช่น มีวัตถุดิบ แรงงาน เป็นต้น 3) ภาษีนำเข้าเป็นศูนย์ ทำให้อุปสรรคนอกเหนือภาษีหมดไป ทำให้มีความได้เปรียบด้านราคาและคุณภาพ ด้านการปรับตัวของ ผู้ประกอบการธุรกิจค้าปลีกในภาคตะวันออกเฉียงเหนือสู่การเป็นประชาคมเศรษฐกิจอาเซียน พบว่า การปรับ ตัวด้านการตลาด ด้านการลงทุน ด้านการบริหารจัดการ ด้านบุคลากร ด้านสารสนเทศ ด้านบริหารสินค้า และ ด้านการบริหารร้านค้ามีการปรับตัวอยู่ในระดับมาก และพบว่าประเภทร้านค้าปลีก และความรู้ความเข้าใจ เกี่ยวกับประชาคมเศรษฐกิจอาเซียนของผู้ประกอบการธุรกิจค้าปลีกในภาคตะวันออกเฉียงเหนือเป็นปัจจัย ที่มีอิทธิพลต่อการปรับตัวสู่การเป็นประชาคมเศรษฐกิจอาเซียน The objectives of this research were to study: 1) the cognition of retail entrepreneurs in the Northeastern part of Thailand toward ASEAN Economic Community 2) the levels of adaptation of retail entrepreneurs in the Northeastern part of Thailand for being a membership to ASEAN Economic Community and 3) the casual factors which influenced the adaptation of retail entrepreneurs in the Northeastern part of Thailand to ASEAN Economic Community. Questionnaire surveys were collected from 900 samples of retail entrepreneurs. The study showed that the first three levels of cognition of retail entrepreneurs regarding the impact of ASEAN Economic Community on retail business were: 1) free trade area for ASEAN investment would allow the competitors to invest in the Country 2) free trade area for ASEAN investment would cause the off-shoring in manufacturing to the appropriate Countries that could offer better deals, such as: raw materials, labors, etc. 3) 0% of import tax would vanish the obstacles relating to the taxes and allow the advantage of price and quality. The study also showed that: the levels of adaptation of retail entrepreneurs in the Northeastern Part of Thailand to ASEAN Economic Community on marketing, investment, management, personnel,information technology, inventory management, and retail management were high. And the results showed that: the type of retail business and the cognition of ASEAN Economic Community of the retail entrepreneurs in Northeast, Which affected to adaptation of the retailing business toward ASEAN Economic Community